Strategi Pelestarian Tradisi Katoba sebagai Media Pendidikan Islam pada Masyarakat Etnis Muna di Sulawesi Tenggara - Rukmina Gonibala; Ardianto Ardianto; Hadirman Hadirman (Institut Agama Islam Negeri (IAIN) Manado, 2018)
ABSTRACT., The purpose of this study was to describe the preservation strategy of the katoba’s tradition as a medium of Islamic education in Muna ethnic communities at Southeast Sulawesi. Katoba was a life cycle tradition that deals with the practice of Islamic values which carried out hereditary by Muna ethnic communities. In Muna ethnic communities, the Katoba tradition was understood as a ritual of